Orthotospovirus disease epidemic: molecular characterization and incidence in peanut crops - De Breuil, Soledad (2020)
Argentina is one of the main peanut (Arachis hypogaea L.) exporting countries with the major peanut-growing area located in the province of Córdoba. During the 2015–2016 growing season, severe outbreaks of an orthotospovirus-like disease occurred in a number of commercial peanut fields. The aim of this work was to determine the prevalence of orthotospoviruses and their incidence in peanut. In DAS-ELISA, all samples collected from symptomatic plants reacted with antisera to groundnut ringspot virus/tomato chlorotic spot virus (GRSV/TCSV) and tomato spotted wilt virus (TSWV). RT-PCR was performed with a single pair of primers for conserved regions of the GRSV, TCSV and TSWV nucleoprotein (N) genes, and digestion with restriction enzymes, allowed the identification of the pathogen asGRSV. The results were confirmed by sequencing of the N gene. Diseased peanut plants were observed in 30 out of 81 surveyed fields located in the north-central region of the peanut-growing area. In that region, the disease incidence was evaluated in four commercial fields, recorded values from 3% to 47.25% with a mean disease incidence of 18.69%. Our study reported for the first time a significant outbreak of GRSV in peanut in Argentina and provide information on the occurrence and distribution of some Orthotospovirus species.